Estimating the Effect of Competitiveness on Turnout across Regime Types. (August 2021) - Eichhorn, Kristin; Linhart, Eric
Electoral turnout as an indicator of political participation, political equality and, thus, democratic performance is one of the most important variables in the study of elections. While numerous studies have contributed to the explanation of electoral turnout, the picture is still incomplete. Notably, a variable which pertains to the core of elections, the competitiveness of electoral races, is not fully understood yet. We contribute to filling this gap by accounting for different effects of competitiveness in democracies and autocracies, as well as against the background of varying institutional settings. Our analyses suggest that vote margins are a suitable measure of competitiveness, but only in democracies with plurality or majority electoral systems. Ex ante measures of competitiveness capture the concept of competitiveness more comprehensively and are applicable across electoral systems and regime types.